Homoleptic and Heteroleptic Substituted Amidomethylpyridine Iron Complexes: Synthesis, Structure and Polymerization of rac‐Lactide. Issue 15 (12th May 2022) - Hashmi, Obaid H.; Capet, Frederic; Visseaux, Marc; Champouret, Yohan
Abstract: The synthesis of iron complexes bearing amidomethylpyridine ligands, one homoleptic [2‐[(2, 6‐iPr2 ‐C6 H3 )NC(Me)]C5 H4 N]2 Fe (1 ) complex and two heteroleptic silylamide iron complexes [2‐[(2, 6‐iPr2 ‐C6 H3 )NC(Me)]‐6‐R‐C5 H4 N]Fe(N(SiMe3 )2 )C5 H5 N (R=H, 2 Py and R=Me, 3 Py ), are described together with their application as catalysts for the Ring‐Opening Polymerization (ROP) of rac ‐lactide ( rac ‐LA). The determination of the crystal structure of the three iron complexes is reported as well as their behavior in solution by means of 1 H NMR studies. All of these complexes have shown to be active for the polymerization of rac ‐LA at 50 °C in toluene, producing, among others, high molecular weight polylactides (PLA) according to SEC analysis, along with a portion of low molecular weight cyclic polymer ( c PLA) on the basis of MALDI spectra. Abstract : The synthesis and characterization of iron complexes bearing amidomethylpyridine ligands are described as well as their application as catalysts for the ring‐opening polymerization (ROP) of rac ‐lactide ( rac ‐LA).